Dietary n-3 Polyunsaturated Fatty Acids in Late Pregnancy and Postpartum Depressive Symptom among Japanese Women - Kobayashi, Minatsu; Ogawa, Kohei; Morisaki, Naho; Tani, Yukako; Horikawa, Reiko; Fujiwara, Takeo (Frontiers in Psychiatry, 2017)
Background: The use of n-3 poly-unsaturated fatty acids (n-3PUFA) in preventive or therapeutic modalities for postpartum depression, especially long-chain types such as eicosapentaenoic acid (EPA) and a docosahexaenoic acid (DHA), is of considerable interest. High n-3PUFA consumption has been reported among pregnant Japanese women. Therefore, analysis of this group could provide important insights into the relationship between postpartum depression and dietary n-3PUFA consumption. To further examine the relationship between the risk of postpartum depression and n-3PUFA consumption, we conducted a prospective hospital-based birth cohort study in Japan. Design and Methods: Our prospective birth cohort study was performed at the National Center for Child Health and Development (NCCHD) in suburban Tokyo, Japan. Dietary n-3PUFA intake during late pregnancy was assessed by a semi-quantitative food questionnaire and participants were categorized by quintile distributions of n-3PUFA intake. A Japanese translation of the Edinburgh Postnatal Depression Scale was used to screen women for postpartum depression at one month after delivery (967 women) and at six months after delivery (710 women). We performed logistic regression analysis to examine the relationship between the risk of postpartum depression and n-3PUFA consumption after adjusting for confounding factors. Results: Significant associations between EPA, DHA and n-3PUFA intakes in late pregnancy and postpartum depression at both one month and six months after delivery were not observed. Conclusions: This prospective study indicated that EPA, DHA and n-3PUFA intake during late pregnancy was not associated with the risk of postpartum depression.